Delivery Notification System Using Web Based - Fatin Najibah, Raduan (2012)
Delivery Notification System is designed to enhanced the current system that already exist in Kolej Kediaman 1(KK1) in Universiti Malaysia Pahang by implementing a notification of incoming parcel/mail to the students’ e-mail as well as to improve the management of mailing at the KK1 office. This system is developed by using web based technique where all the programming and data store are using Hypertext Preprocessor (PHP) and MySql respectively. Besides, barcode technology is applied which could enhance the security level of the system. The results of this implementation are the students of KK1 will get an e-mail notification when their parcel/mail is arrived at the university thus the problem of time wasting for unnecessary checking for the parcel that has not arrived has been solved. Furthermore, the management of the mailing system at the KK1 can be improved and save times to record the incoming parcels. Lastly, DNS is a system that could improve the existing mailing system in UMP and hope that the system could be enhanced in the future.